Students’ Perception of Water Safety Education: A Case Study in Selangor, Malaysia - Yusoff, Aziyah; Ibrahim, Nor Addha; Ali, Aliza; Rahmat, Siti Nor Shaadah; Joned, Siti A'ida; Yusoff, Azimah (International Journal of Social Sciences Review, 2024)
The safety of children near water is crucial to avoid drowning, a major cause of death among children worldwide. Drowning incidents are a significant issue in Malaysia, especially among young people. The greatest obstacle to the development of policy for water safety among school children is lack of awareness or knowledge of water safety.  This study represents an attempt to measure attitudes towards waters safety and risk of drowning in the District of Gombak in Malaysia. Given the urgency of the matter, immediate attention and action are required. Therefore, this paper seeks to highlight the pressing nature of water safety concerns among school children and assess whether implementing a water safety education program can substantially enhance knowledge levels, thus reducing drowning incidents among children. Yet, drowning in Malaysia still doesn't get enough attention. The sample of the study was 502 school children from a school in the district in Selangor. Purposive sampling was selected. The major findings that emerged were as below: a) the respondents prefer to swim alone. b) They are less favor in of wearing life jackets. c) They prefer to swim without having adults around them. d) They are prone to swim without learning to swim. e) No association between students’ attitudes towards water safety and sex.  The urgency of this research is to address water safety issues among school children.